The association between subjective socioeconomic status and depressive symptoms in women of reproductive age: the chain mediating effects of marital satisfaction and well-being - Han, Ruiyang; Ding, Xiao; Yang, Manzhou; Feng, Wenjia; Wang, Yan; Cai, Weiqin; Gao, Qianqian; Han, Yuanzhuo; Hu, Youli; Ma, Anning (Frontiers in Psychology, 2025)
ObjectiveThe underlying mechanism between subjective socioeconomic status (SSS) and depressive symptoms among women of reproductive age in China is not fully. This study aims to explore the mediating roles of marital satisfaction and well-being in the association between SSS and depressive symptoms.MethodsA total of 4,219 women of reproductive age were selected from the 2022 China Family Panel Studies. Data related to SSS, marital satisfaction, well-being, and depressive symptoms were extracted. Spearman rank regression and bootstrap methods were used to analyze the chain mediation effects of SSS, marital satisfaction, well-being, and depressive symptoms.Results(1) SSS, marital satisfaction, well-being, and depressive symptoms were significantly correlated (p < 0.01). (2) SSS directly affected depressive symptoms (β = −0.1092, p < 0.001). (3) Marital satisfaction (β = −0.0873, p < 0.001) and well-being (β = −0.0867, p < 0.001) each played a mediating role in the effect of SSS on depressive symptoms. (4) Marital satisfaction and well-being played a chain mediating role in the association between SSS and depressive symptoms in women of reproductive age (β = −0.0703, p < 0.001).ConclusionThere is a chain mediation effect between SSS, marital satisfaction, well-being, and depressive symptoms in women of reproductive age. Improvement in SSS can enhance marital satisfaction, which in turn increases well-being, ultimately alleviating depressive symptoms in women of reproductive age.